(untitled) (Journal of Health, Population and Nutrition, 2011)
The role of physical violence during pregnancy on receipt of prenatal care is poorly understood, particularly for South Asian countries that have high levels of both fertility and domestic violence. Data from the 1998/1999 Indian National Family Health Survey and a 2002/2003 follow-up survey that re-interviewed women in four states were analyzed, examining the association between physical violence during pregnancy and the uptake of prenatal care. Women who experienced physical violence during pregnancy were less likely to receive prenatal care, less likely to receive a home-visit from a health worker for a prenatal check-up, less likely to receive at least three prenatal care visits, and less likely to initiate prenatal care early in the pregnancy. This study highlighted the constraining effect that the experience of physical domestic violence during pregnancy had on the uptake of prenatal care for women in rural India. Maternal health services must recognize the unique needs of women experiencing violence from their intimate partners. Key words: Domestic violence; Pregnancy; Prenatal care; India DOI: http://dx.doi.org/10.3329/jhpn.v29i3.7872 J HEALTH POPUL NUTR 2011 Jun;29(3):245-254